Implied threats of the Red Sea crisis to global maritime transport: amplified carbon emissions and possible carbon pricing dysfunction - Peng, He; Wang, Meng; An, Chunjiang (Environmental research letters, 2024)
Recent military acts in the Red Sea and Gulf of Aden are forcing merchant ships to reroute, thereby driving up international shipping rates, prolonging delivery dates, and causing additional greenhouse gas emissions. Utilizing the European Union (EU) Monitoring, Reporting, and Verification emissions database and real time Automatic Identification System data, this study conducted frequency analysis and causative investigation on container ships circumnavigating the Cape of Good Hope. The findings indicate that the current policy framework under the EU Emissions Trading System (EU-ETS) poses a higher risk of carbon leakage, particularly for medium and small-sized container ships, thereby undermining the effectiveness of the nascent EU maritime carbon pricing. If the crisis continues, combined with anticipated tighter emission regulations, this risk is expected to escalate. International maritime policy administrators should make timely adjustments in response to the chain reactions caused by war, enhancing the robustness of cross-regional carbon pricing.